Estimation of Local Mechanical Properties by Small Punch Test in Welded Joints of Maraging C250 Steel - Svoboda, Hernán Gabriel; Duran, Mercedes Andrea; Belzunce, Francisco Javier; Rodríguez González, María Cristina (Springer, 2024)
Local mechanical properties (LMPs) of welded joints are strongly affected by the experienced thermal cycle, controlling the global behavior of the joint. In this work, LMP of GTAW-pulsed welded joints of maraging C250 steel was studied by small punch tests (SPTs) throughout the welded joint, both in as welded (AW) and post-weld heat-treated (PWHT) conditions. LMPs were estimated by SPT from the weld metal up to the base metal, obtaining the yield and tensile strength and elongation to fracture for each zone. The results were compared with microhardness profiles, and microstructural analysis was also done to correlate it with the peak temperatures reached in each zone of the welded joint. For AW conditions, the weld metal and austenitized heat-affected zone show the lowest strength values and the highest ductility. Then, a transition to the highest local strength at the zone reached at the position that experienced Ac1 temperature. Finally, a decrease in strength values up to reach the base metal take place in the subcritical heat-affected zone. The local strength estimated by SPT was considerably improved after PWHT, reaching the base material strength in aged condition except in the weld metal zone, mainly associated with the presence of reverted austenite. This zone controls the mechanical properties of the welded joints. In the PWHT condition, the welded joint achieved an efficiency of 95%. SPT has shown its capacity for the estimation of LMP of welded joints of ultrahigh strength maraging steels, providing additional information of the local mechanical behavior.
Keywords: Ingeniería y tecnología::Ingeniería de materiales